Sexual uses of drug and alcohol among men who have sex with men in China: implications for HIV prevention - Wang, Jinshen; Zhao, Peizhen; Xu, Wenqian; Wang, Cheng (BMC infectious diseases, 2022)
Sexual uses of alcohol and drugs are pervasive among men who have sex with men (MSM) and associated with increased risk of HIV infection. However, there are limited studies related to sexual uses of alcohol and drugs among MSM in China. This study aims to describe the pattern of alcohol use, drug use, and multi-drug use during sex among Chinese MSM and to examine the association between condomless anal intercourse, group sex, commercial sex and HIV infection. We conducted an online cross-sectional survey in China. Characteristics on social-demographic, sexual behaviors, and sexual uses of alcohol and drugs were collected. The associations with high-risk sexual behaviors and HIV infection were analyzed with multivariable logistic regression. A total of 699 MSM were included in this study. About 39.5% (230/582) of men reported sexual alcohol use in the past three months and 50.8% (355/699) reported sexual drug use. Of those reporting sexual drug use, around 10.7% (38/355) reported having multi-drug use. Factors associated with both sexual uses of alcohol and drugs included: reporting more male sexual partners (alcohol: adjusted odds ratio [aOR] = 1.77; drug: aOR = 2.12), reporting condomless anal intercourse in the past three months (alcohol: aOR = 2.08; drug: aOR = 2.08), having ever engaged in group sex (alcohol: aOR = 2.04; drug: aOR = 5.22; multi-drug: aOR = 3.52) and commercial sex (alcohol: aOR = 4.43; drug: aOR = 4.22 multi-drug: aOR = 5.07). Sexual drug use was also correlated with reported HIV-positive status (drug: aOR = 2.53, 95% CI:1.31-4.90). Sexual uses of alcohol and drugs are prevalent among Chinese MSM. Interventions to reduce the sexual use of alcohol and other drugs may be warranted among MSM in China.